Réplicas entre Cuba y Nicaragua. Relaciones destotalizantes en la región - Celia Irina González Álvarez (Confluenze)
I am interested in analyzing the replica as a condensing element of the encounter scene between Cuban and Nicaraguan artists. At the same time, I intend to understand artistic practices as producers of de-totalizing exchange relations. I argue that the replica, as a mimetic reproduction of the original, also includes the effects of the copied object, in this case, the capacity to produce de-totalizing relations. By this I mean the capacity to create alliances that defy the division of the population into enemies and militants, revolutionaries and counterrevolutionaries, the logic that sustains the One Party.